56 Parent and health professional experiences and views of genome sequencing for rapid diagnosis in critically ill children. (22nd November 2019) - Hill, Melissa; Hammond, Jennifer; Lewis, Celine; Mellis, Rhiannon; Clement, Emma; Chitty, Lyn
Abstract : The Rapid Paediatric Sequencing (RaPS) study at GOSH offers trio genome sequencing (GS) for rapid diagnosis of critically ill children with a likely monogenic disorder. Main findings and medically actionable secondary findings are reported. Here we describe a qualitative study exploring parental and professional perceptions of RaPS, the psychosocial impact and potential for harm. Semi-structured interviews are being conducted with: (1) Parents of children undergoing RaPS and (2) Professionals (scientists, genetics clinicians and non-genetic clinicians). Interviews are recorded, transcribed and analysed using thematic analysis. To date, 19 professionals and 6 parents had largely positive views about RaPS, describing clinical, practical and emotional benefits from the opportunity to obtain a rapid diagnosis. Parental stress surrounding their child's illness complicates decision-making for GS. Professionals note these parents are desperate, may say yes to any test and have high expectations of receiving a diagnosis. Parents want more information, particularly about limitations and secondary findings. The importance of multidisciplinary team working to triage patients, interpret results and deliver GS within a rapid timeframe has been highlighted. Our findings give insight into the perceived usefulness of rapid genome sequencing for critically ill children and highlights the challenges of facilitating informed decision making in critical care settings.